The Phenomenon Of Divorce For Women Migrant Workers in Muncar Banyuwangi - Eko Setiawan (Journal of Southeast Asian Islam and Society, 2025)
The phenomenon of divorce is rife among women migrant workers in Banyuwangi. It is a form of divorce but accompanied by the provision of material compensation, a cultural term that is widely used by most Banyuwangi people. In simple terms, the technical definition of divorce is filed by the wife so that the marriage bond with her husband can be severed religiously and state administration. Then the wife as the plaintiff is burdened with the obligation to bear all costs in the divorce lawsuit process filed. This type of field research aims to study natural environmental phenomena based on data obtained on natural objects of research in the field. Data collection methods use observation, in-depth interviews, documentation. Data analysis using interactive models, including: data reduction, data presentation, conclusion drawing. The results showed that the most dominant economic factor as a trigger for divorce cases was caused by wives who were dissatisfied with their husband's relatively small income. The role of mediators in mediation sessions in religious courts as an alternative to reducing divorce rates, so that household arks can survive.